Rational factors in the spiritual journey of embracing Islam - Suraya Sintang; Khadijah Mohd Hambali (Penerbit Akademi Baru, 2016)
The studies on conversion to Islam in multi-faiths and multi-nations show that there are many pushed and pulled factors of religious shift either as rational factors or relational ones. The rational factors which is induced by intellectual search for embracing Islam as alternative live has become a focal point of discussion in this paper. Analyzing rational factors from various experiences of new Muslims in multi-nations’ biographical narratives will significantly clarify the misperceptions that marriage is the main factor of becoming Muslim. This paper highlights the key themes of Islam which are believed to be the rational factors by those individuals to embrace Islam. The study on the rational factors of embracing Islam is carried out by examining the secondary and primary data of new Muslim’s biographical narratives. Embracing Islam through the means of rational factors is induced by two contributing elements; intellectual connection to Islam and guide of life. It is to say that, behind the spiritual tradition of Islam, there is the rationality that clarify the content of Islamic teachings which bring about the potential convert to think deeper on making a choice for a new alternative way of life to embrace Islam. This intellectual conversion has helped much on the new Muslim to face the challenge for being a practicing Muslim as the religious choice is rational.